Currency Moderates Brand Ambassador And Co-creation Towards Customer Loyalty For Scarlett Whitening Products (Study of Scarlett Whitening Users in The Bekasi Regency Area) - Surya Bintarti; Chairunnisa Saliasna (Dinasti Publisher, 2024)
The research method used is quantitative method, where the object of this research is Scarlett Whitening users in the Bekasi Regency area. The sampling technique used is nonprobability sampling, specifically purposive sampling method. The sample size for this research is 114 people. This study examines correlation and regression using the SMARTPLS 4.0 program to test validity, reliability, goodness of fit model, and hypotheses. The conclusions drawn from this research are as follows: 1) Brand ambassadors employed by Scarlett Whitening have a positive impact on customer loyalty, although the effect is relatively weak. 2) Brand ambassadors moderated by currency have a positive impact on customer loyalty for Scarlett Whitening, although the effect is relatively weak. 3) Co-creation shows a strong positive influence on customer loyalty. 4) However, there is a component like co-creation moderated by currency that has a negative and insignificant effect.